Replacing dried skim milk with select menhaden fish meal in a high nutrient density diet - G R Stoner; Jim L Nelssen; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1988)
A growth study was conducted to evaluate the possibility of replacing dried skim milk (DSM) with select menhaden fish (SMFM) in a high nutrient density diet. A total of 210, 3wk- old weaned pigs was utilized. Diets were formulated by: 1) replacing 50 or 100% of the DSM with SMFM and maintaining the lactose content of the diet by increasing the dried whey inclusion or 2) by replacing 50 or 100% of the DSM with SMFM and corn. These formulations yielded three diets containing 24% lactose, one diet containing 19% lactose, and one containing 14% lactose. Growth performance was similar on diets containing 19 or 24% lactose, but was depressed (P<.05) on the diet containing 14% lactose. These results indicate that SMFM can be used to replace DSM, but the lactose content of the diet must be considered as well.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Pigs; Early weaning; Fish meal; Dried skim milk; Dried whey; Lactose